Investigation of gold nanorods as a sensing material in plasmonic sensor for triclopyr butotyl detection - Md Shah, Nur Zehan An’nisa (2020)
Gold nanorods (GNRs) have a unique optical property of metal nanoparticles (MNPs) due to the localised surface plasmon resonance (LSPR) effect, which depends on the size, shape and dielectric property of the surrounding medium. LSPR, or commonly known as the plasmonic effect, refers to the optical phenomena resulting from the interaction of free electrons on a nano-sized metal surface with incident light at specific wavelengths. The plasmonic effect of rod-shaped nanoparticles shows dual absorption bands corresponding to transverse surface plasmon resonance (t-SPR) and longitudinal surface plasmon resonance (l-SPR). These two bands are sensitive to size changes and the surrounding medium’s refractive index. In GNR formation, particles size, homogeneity and shape are crucial elements to be investigated during the synthesis process. Therefore, three parameters are studied in this research, which are centrifugation speed, seed solution concentration and growth solution ageing period. Through the variation of parameters during the synthesis procedure, the optimum GNRs with a surface density of 74.81 %, an average length of 59.80 ± 0.53 nm and an average width of 14.14 ± 0.19 nm produce an aspect ratio of 4.23 ± 0.36 via the seedmediated growth method (SMGM). The optimum GNR sample is prepared by adding 10 µl of a seed solution into a raw growth solution and left undisturbed for 20 hours and then centrifuged at a rotational speed of 5000 rpm. The optical spectrum from that sample exhibits two plasmon bands at the transverse axis of 535.02 nm and the longitudinal axis of 782.65 nm. For sensing application, the GNRs are used as a sensing material to detect the targeted analyte, namely triclopyr butotyl (Cଵଷ Hଵ଺ClଷNOସ). The sensitivity, stability and repeatability of GNRs in deionized water and triclopyr butotyl medium is studied by observing the changes in the absorption intensity and the peak position of the plasmon resonance. The optical response of 10 % triclopyr butotyl without GNRs shows no significant peaks and proves that GNRs are able to increase the ability of detection through the plasmonic effect. In sensitivity testing, it is found that the presence of triclopyr butotyl changes the absorption intensity and shifts the resonance peak position of the GNRs. The vi detection limit of GNRs is as low as 3 %. Furthermore, the GNRs depict good response during 600 seconds of the stability test. Moreover, the fast response and recovery time in the change of medium observed in five cycles show good repeatability of GNRs.